An explorative study of psychological and social factors impacting littering behavior in Vietnam - Zhang, Anran; Pang, Bo; Kim, Jeawon; Nguyen, Tuyet-Mai; Nham, Phong Tuan (Frontiers in Psychology, 2022)
Littering is a worldwide problem and Vietnam is one of the most affected countries. To enact change, not only individual cognitive determinants but also social and natural-, or environment-related variables should be taken into consideration. Although there is a large body of literature researching littering, most researchers do not distinguish the level of these factors. Thus, this research aims to investigate the interactive mechanism of these different level factors influencing the intention of the Vietnamese to stop littering, with the multi-level social-ecological model used to guide model building. The data were collected through a self-reported online questionnaire and the Partial Least Squares Structural Equation Modelling (PLS-SEM) method was employed to examine the proposed conceptual framework. The results indicated that perceived behavioral control and connectedness to nature are the two main factors influencing the Vietnamese people’s intention to stop littering. Multi-group analysis results suggested the moderating effects of injunctive and descriptive norms. This research proposed a new conceptual framework and achieved unique insights into littering behavior in Vietnam, which could benefit and guide behavioral change experts, academics, and practitioners to design appropriate marketing strategies/campaigns to reduce littering.